Structural engineering formulas - Mikhelson, Ilya; Hicks, Tyler Gregory (McGraw-Hill's AccessEngineering, 2013)
PRACTICAL, PORTABLE, AND PACKED WITH UP-TO-DATE STRUCTURAL ENGINEERING FORMULAS Thoroughly revised with more than 300 new formulas,this compact yet comprehensive compilation puts essential data related to the design and analysis of engineeringstructures at your fingertips.StructuralEngineering Formulas, Second Edition covers a wide range of topics, including statics, soils, foundations, retaining structures, pipes, and tunnels, and explains the use and application of each ready-to-use formula. This time-saving reference for civil engineers is alsoinvaluable to students and those studying for licensing exams. COVERAGE INCLUDES: Stress and strain-methods of analysis | Properties of geometric sections | Beams--diagrams and formulas for various loading conditions | Frames--diagrams and formulas for various static loading conditions | Arches--diagrams and formulas for various loading conditions | Trusses--method of joints and method of section analysis | Plates--bending moments for various support and loading conditions | Soils | Foundations | Retaining structures | Pipes and tunnels--bending moments for various static loading conditions